Analisis Multivariat Hubungan Usia Dan Self-Management Dengan Tekanan Darah Tidak Terkontrol Pada Perempuan Hipertensi: Studi Kasus-Kontrol - Riyanto; Rosalinna; Ria Kuriniarum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Uncontrolled hypertension is one of the main factors that increases the risk of cardiovascular morbidity and mortality in women. Self-management plays an important role in blood pressure control, but evidence on the independent contribution of its dimensions remains limited. This study aims to analyze the relationship between age and dimensions of self-management with blood pressure control in women with hypertension at the Yosomulyo Community Health Center, Metro City, Lampung, Indonesia. Methods: This study used a case-control design involving 62 women with hypertension: 31 cases (uncontrolled) and 31 controls (controlled). Data were collected through structured interviews using a validated questionnaire that measured self-management: emotional, instrumental, and informational support, as well as self-assessment. Analyses were performed using self-management tests and multiple logistic regression. Results are presented as odds ratios (OR), adjusted odds ratios (AOR), and 95% confidence intervals (95% CI). The results of the bivariate analysis showed a significant association between age >35 years (p = 0.004; OR = 4.75; 95% CI: 1.58–14.31) and low self-management: informational support (p = 0.005; OR = 4.44; 95% CI: 1.53–12.94) with uncontrolled hypertension. In the multivariate analysis, age >35 years (p = 0.002; AOR = 6.54; 95% CI: 1.96–21.74) and low self-management: instrumental support (p = 0.023; AOR = 5.24; 95% CI: 1.25–22.22) remained independently associated with uncontrolled hypertension. The study’s conclusions indicate that older age and low instrumental support are independent predictors of uncontrolled hypertension. Strengthening practical support within self-management interventions could improve the success of blood pressure control among women with hypertension. Keywords: hypertension; blood pressure control; self-management; instrumental support; case-control study.